Regionalism and realism : a study of governments in the New York metropolitan area - Benjamin, Gerald; Nathan, Richard P.; Century Foundation; Brookings Institution (Washington, DC : Brookings Institution Press, 2001)
Annotation Drawing on the history of state and local government in the New York Tri-State metropolitan region, the authors present a pathbreaking new theory about the values reformers must understand and balance in order to tackle the hard challenges of reforming and regionalizing local governance in the complex, dynamic world of American politics and public policy. Their examination of the way 2,179 local governments in the Tri-State region have evolved over more than a century pays special attention to New York City, but is applicable to other metropolitan areas. It brings to life ideas that are crucial to a subject that in the academic literature is often treated in a way that is abstract and hard to grasp. This is a valuable book for scholars, political leaders, and students interested in regionalism in metropolitan America and in the fascinating history and governance of the nation's largest city and its vast metropolitan region.
9 Two Approaches: Bottom Up and Top Down -- PART FIVE: The Nation in the Regional Arena -- 10 The Case of Solid Waste -- PART SIX: Conclusion -- 11 Lessons for the Future -- Notes -- Index.
"A Century Foundation Book."
Includes bibliographical references (pages 269-299) and index.
Print version record.
English.
JSTOR
Keywords: Local government -- New York (State) -- New York Metropolitan Area; Regionalism -- New York (State) -- New York Metropolitan Area; Intergovernmental cooperation -- New York (State) -- New York Metropolitan Area; POLITICAL SCIENCE -- Government -- Local; POLITICAL SCIENCE -- Government -- State & Provincial; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; Intergovernmental cooperation; Local government; Regionalism; New York (State) -- New York Metropolitan Area